Interpreting Disability in the Old Testament – A Hermeneutical Analysis of Inclusion and Moral Interpretation - EKMEKCIOGLU, Lilla (Studia Universitatis Babes-Bolyai Theologia Reformata Transylvanica, 2026)
This study examines the representation of disability in the Old Testament and its influence on later theological and cultural interpretations. Employing a qualitative, hermeneutical, and context-sensitive approach, it analyses narrative, legal, cultic, prophetic, and wisdom texts that refer to physical, sensory, and cognitive impairments. Particular attention is given to the literary diversity of the biblical corpus and to the ancient Near Eastern context, in which no unified concept of “disability” existed. The study systematically identifies and classifies relevant passages, highlighting the multiple layers of meaning through which bodily difference is articulated. The findings demonstrate that the Old Testament presents disability in diverse and often overlapping ways, including descriptive accounts of human vulnerability and aging, identity-forming experiences associated with divine encounter, ethical imperatives emphasizing communal responsibility, and metaphorical expressions of spiritual insensitivity or disobedience. Legal and narrative traditions frequently foreground protection, inclusion, and care, positioning persons with impairments within broader categories of social vulnerability rather than as objects of moral condemnation. At the same time, certain cultic regulations introduce restrictions tied to ritual roles, reflecting symbolic notions of holiness rather than comprehensive social exclusion. Although some covenantal curse texts and disciplinary narratives portray impairment as a form of divine punishment, these instances are contextually bounded and serve specific rhetorical and theological purposes. They do not constitute a consistent or dominant biblical doctrine of disability. Overall, the study argues that the moral model linking disability with sin and punishment emerges primarily from later interpretive traditions, rather than from the internal logic of the Old Testament texts themselves, which instead reflect a plurality of perspectives shaped by genre, context, and theological intent.